Admission Point-of-Care Testing for the Clinical Care of Children with Cerebral Malaria - David Wichman; Geoffrey Guenther; Nthambose M. Simango; Mengxin Yu; Dylan Small; Olivia D. Findorff; Nathaniel O. Amoah; Rohini Dasan; Karl B. Seydel; Douglas G. Postels; Nicole F. O’Brien (Tropical Medicine and Infectious Disease, 2024)
Point-of-care testing (PoCT), an alternative to laboratory-based testing, may be useful in the clinical care of critically ill children in resource-limited settings. We evaluated the clinical utility of PoCT in the care of 193 Malawian children treated for World Health Organization-defined cerebral malaria (CM) between March 2019 and May 2023. We assessed the frequency of abnormal PoCT results and the clinical interventions performed in response to these abnormalities. We determined the association between abnormal PoCT results and patient outcomes. Overall, 52.1% of all PoCT results were abnormal. Of the children with abnormal results, clinical interventions occurred in 16.9%. Interventions most commonly followed abnormal results for PoCT glucose (100.0% of the patients had treatment for hypoglycemia), potassium (32.1%), lactate (22.0%), and creatinine (16.3%). Patients with hypoglycemia, hyperlactatemia, and hypocalcemia had a higher mortality risk than children with normal values. Future studies are needed to determine whether obtaining laboratory values using PoCT and the clinical response to these interventions modify outcomes in critically ill African children with CM.